Characterization of Anopheles funestus Larval Habitats in Fiyoni, Kwale County, Kenya: Insights into Malaria Vector Ecology and Control - Clifton Omondi; Dr. James Nonoh; Dr. Regina Ntabo (European Journal of Ecology, 2023)
The breeding of malaria-spreading vectors such as Anopheles funestus is influenced by various environmental factors that contribute indirectly to the transmission of the Plasmodium parasite. However, there is limited knowledge of larval habitat ecology that hinder prevention and control of mosquito-borne diseases. This study aimed to characterize larval habitats based on physicochemical and habitat characteristics, considering the abundance of A. funestus.  A cross-sectional survey method was used to collect data on the established transects. Physical parameters (water temperature, pH, conductivity, and total dissolved solids) were measured using a 5-in-1 meter probe. Levels of chemical parameters (sulphate, COD, and BOD) were determined in the laboratory using standard methods. Observations were also made on habitat characteristics (including watercolor, habitat size, and canopy). There was significant effect (P<0.05) of conductivity, pH, sulphate, COD, and BOD on the number of A. funestus larvae. Water samples with a high population of A. funestus larvae were found to have higher conductivity (Me of 470.5), TDS (Me = 235), and pH levels (Me of 6.71). Conversely, water samples with a high population of non-Anopheles funestus larvae were found to have higher COD (Me of 843.20), BOD (Me of 367.2), and SO4 levels (Me of 11.3). A significant correlation (p<0.5) existed between A. funestus larvae and physical water parameters. For instance, Anopheles funestus larvae was high (Me of 36.85) in stagnant water and in semi-permanent water (Me of 47.37). The study demonstrates that both physicochemical and habitat parameters significantly influence the abundance of Anopheles funestus larvae in larval habitats. Parameters such as conductivity, pH, total dissolved solids, sulphate, COD, BOD, watercolor, depth, distance from the homestead, and habitat size were found to be important in determining the presence of A. funestus larvae. Therefore, vector control strategies should include larval source management by targeting rivers and other water bodies to prevent the emergence of Anopheles funestus.